Ta’alum Al-Lughah Al-Arabiyyah Li Aghradl Khashah: Akadimi Wa Mihni - Novita Rahmi; Albarra Sarbaini; J. Sutarjo; Nawang Wulandari (Institut Agama Islam Negeri (IAIN) Metro, 2022)
Arabic has a function and essence for the life of Islamic communication, but because of its nature which is in the midst of an ongoing educational tradition today, it requires various innovations, as a logical consequence of the development of science and technology. The development of science and technology is so rapid for human life, it is necessary to make efforts on Arabic language teaching technicians who adapt to their respective fields and competencies. Then the purpose of learning Arabic with this specific purpose is to develop the professional abilities and academic potential of students.This type of research is descriptive qualitative research, namely a research conducted systematically by using library data using data collection tools, namely, observation, and documentation. This study provides a goal-based Arabic learning model to be achieved which is called Arabic learning for special purposes. This learning is more directed at learning Arabic for a certain scope and context, for example for work or professions and also in the academic field.